Investigation of the Correspondence between Problems Solving Based on Cognitive Psychology Tests and Programming Course Results - Katona, Jozsef; Ujbanyi, Tibor; Kovari, Attila (International journal of emerging technologies in learning, 2015)
Nowadays the education of different programming and software development courses is more difficult. Students are not able to learn solutions and techniques that are needed to solve a problem even though their prominent interests and diligence. In cognitive psychology, there are some test procedures which can measure the problem solving ability of a test subject. In engineering education there is no field where problem solving skills are unnecessary, the test procedures of cognitive psychology adumbrate the success of a programming course. The primary aim of this article is to examine the relationship between the test results of the measurement procedure of cognitive psychology and the results of success of programming courses. If there is correlation between the two, the measurement method can be used as a filter in the recruitment process in secondary schools, colleges or universities.